25-Hydroxycholesterol exerts both a cox-2-dependent transient proliferative effect and cox-2-independent cytotoxic effect on bovine endothelial cells in a time- and cell-type-dependent manner - Nguyen, Vicky PKH; Chen, Stephen H; Pizzuto, Katerina; Cantarutti, Alyssa; Terminesi, Alyssa; Mendonca, Cassandra; Dumont, Daniel J (Vascular Cell, 2010)
Abstract Background 25-hydroxycholesterol (25-OHC) is a product of oxidation of dietary cholesterol present in human plasma. 25-OHC and other oxidized forms of cholesterol are implicated in modulating inflammatory responses involved in development of atherosclerosis and colon carcinogenesis. Methods Primary lymphatic, venous and arterial endothelial cells isolated from bovine mesentery (bmLEC, bmVEC, bmAEC) were treated with 25-OHC and tested for several different cellular parameters. Results We found 25-OHC to be a potent inducer of cyclooxygenase-2 (Cox-2, prostaglandin G-H synthase-2) expression in bovine mesenteric lymphatic, venous, and arterial endothelial cells. The induction of Cox-2 expression in endothelial cells by 25-OHC led to an initial increase in cellular proliferation that was inhibited by the Cox-2 selective inhibitor celecoxib (Celebrex). Prolonged exposure to 25-OHC was cytotoxic. Furthermore, endothelial cells induced to express Cox-2 by 25-OHC were more sensitive to the effects of the Cox-2 selective inhibitor celecoxib (Celebrex). These results suggest that some effects of 25-OHC on cells may be dependent on Cox-2 enzymatic activity. Conclusions Cox-2 dependent elevating effects of 25-OHC on endothelial cell proliferation was transient. Prolonged exposure to 25-OHC caused cell death and enhanced celecoxib-induced cell death in a cell-type dependent manner. The lack of uniform response by the three endothelial cell types examined suggests that our model system of primary cultures of bmLECs, bmVECs, and bmAECs may aid the evaluation of celecoxib in inhibiting proliferation of different types of tumour-associated endothelial cells.